Pelatihan Penulisan Artikel Ilmiah dan Pemanfaatan Alat Bantu Penulisan Artikel Ilmiah untuk Mahasiswa - Deny Hadi Siswanto; Samsinar; Aldo Setiawan; Nur Wahyuni; Puguh Wahyu Prasetyo (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
The objectives of this activity are: (1) to provide understanding to undergraduate students about scientific article writing; (2) to comprehend the process of publishing scientific articles in accredited and non-accredited national journals; (3) to serve as a motivational platform for students to engage in scientific article writing. The methods employed in conducting this Community Service (PKM) activity include lectures and demonstrations. The activity took place via Zoom Meeting on June 3, 2023. The participants involved in this activity consisted of 130 undergraduate students from various universities in Indonesia. The first session covered the topic of choosing accredited national journals and scientific article writing, which includes how to write, how to choose Sinta accredited and unaccredited journals and things that must be considered in writing scientific papers. The second session focused on tools in scientific writing," discussing the use of writing tools such as Mendeley, Publish or Perish, and Quillbot. The result of this training is that students have increased knowledge of writing scientific papers as well as the use of scientific writing tools and can make good can make scientific papers well.